Analisis Kebutuhan Media Chrono E-Puzzle Pada Materi Proklamasi Kemerdekaan Indonesia di SMA - Anjela, Anjela; Afriani, Rini (Jurusan Sejarah FIS UNP, 2025)
This research is motivated by the low level of students’ chronological thinking skills in history learning, which has been dominated by lectures and conventional media such as PowerPoint slides containing long texts. Such conditions make students less active and relatively passive during learning activities. This study aims to analyze the need for an innovative learning medium called Chrono E-Puzzle to improve senior high school students’ chronological thinking skills. The research applied a mixed-method approach (quantitative–qualitative). Data were collected through observation, interviews, and a test using Google Form involving 25 eleventh-grade students of SMA Negeri 7 Padang and a history teacher. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed that: (1) teachers still rely heavily on lectures with monotonous media; (2) students’ chronological thinking skills are relatively low, with only 12% able to correctly sequence the proclamation events; (3) students find it difficult to understand cause–effect relationships within historical contexts; and (4) there is a strong need for interactive and innovative learning media to enhance chronological thinking skills. These results highlight the urgency of developing Chrono E-Puzzle as an engaging, interactive, and meaningful history learning medium.